Peningkatan Kemampuan Pengelolaan Keuangan Syariah Pada Koperasi As Sakinah Sidoarjo - Renny Oktafia; Nihlatul Qudus SN; Muhammad Yani (Janaka, Jurnal Pengabdian Masyarakat, 2020)
Mitra is one of the sharia microfinance institutions in Sidoarjo, Koperasi As Sakinah only for a few years established itself as a sharia cooperative. Where the partners still need to continue to improve their abilities in Islamic financial management. This is intended, so that administrators and managers can manage finances in their institutions in accordance with sharia contracts. In addition, it can continue to innovate product development according to the needs of customers or members. Therefore, to improve the management skills of Islamic finance, for the management and manager of the cooperative, it is necessary to carry out training in Islamic financial recording. In carrying out this training activity, following several stages, namely the needs analysis, the training design stage, the implementation stage, the testing phase, the assistance and maintenance stage. In this activity, more than 50% of the insights and skills of Islamic financial management have been achieved in the management and management of cooperatives. This shows that there has been a significant increase in the ability of cooperative administrators and managers, in managing Islamic finance in their institutions, after participating in and implementing training materials.